Perlindungan Hukum Bagi Pemenang Lelang Yang Barangnya Masih Dimiliki Debitur: PERLINDUNGAN HUKUM BAGI PEMENANG LELANG YANG BARANGNYA MASIH DIMILIKI DEBITUR - Syamsul -; Ismail Pettanase; K.A. Novianysah; Muhammad Adi Saputra (Universitas Muhammadiyah Kotabumi, 2023)
An auction is a sale of goods open to the public with an increasing or decreasing written and/or oral price offer to reach the highest price preceded by an auction announcement. The auction is held openly and there is no priority among the bidders or bidders. The problem that occurs in the community in the banking world is that the debtor is not the owner of the guarantee so that if the debtor defaults the Auction Center finds it difficult to auction the execution of the mortgage object. Even though the collateral owner signs the deed of granting the mortgage right which has been registered at the land agency office, so that the auction winner cannot take possession of the auction object. The legal research method used is normative-empirical (applied) examining the use of positive legal provisions (legislation) and factual clauses in every legal phenomenon that occurs in society with a predetermined goal. Auction winners are given security and legal protection. The auction seller has a legal obligation to uphold the rights of the winning bidder. The pre-auction and post-auction implementation of the regulations reflect this.